PERENCANAAN PEMBELAJARAN KREATIF - Alifia, Khoirrunnnisa; Lantera, Lantera; Kirana, Cinta; Pranatalia Sab’ah, Mutia; Putri Juliani Ajeng Pinasti; Fahmi , Fahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning planning often falls into rigid administrative routines, failing to accommodate the dynamics of student needs in the digital era. This research aims to analyze creative learning planning strategies that accommodate diverse learning styles and evaluate the effectiveness of project-based learning and design thinking methods in instructional design. This study employs library research with a qualitative descriptive approach. Data were collected through documentation studies of primary sources, such as educational regulations, and secondary sources, including reputable journals and scientific books. Content analysis and thematic analysis were applied to interpret the findings. The results indicate that creative learning planning integrates five main pillars: material flexibility, media variety, interactive scenarios, instructional differentiation, and authentic evaluation. The integration of technology and the